Economic Shifts and Labor Dynamics from Bus Corridor IV: Pergeseran Ekonomi dan Dinamika Ketenagakerjaan dari Koridor Bus IV - Heni Niswatin; Sishadiyati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Public transportation plays a pivotal role in enhancing labor mobility and supporting regional economic productivity. Specific Background: In East Java, the development of the Trans Jatim Corridor IV Bus—connecting key economic and industrial zones in Gresik and Lamongan—was introduced to address mobility challenges in non-metropolitan coastal regions. Knowledge Gap: Despite growing interest in urban transit’s economic effects, limited research has explored its impact on labor dynamics in semi-urban or rural coastal areas like Lamongan. Aims: This study aims to quantitatively assess how the Trans Jatim Corridor IV Bus affects labor mobility and economic productivity in Lamongan Regency. Results: Findings reveal that public transport development significantly enhances workforce mobility (R² = 0.741) and economic productivity (R² = 0.615), demonstrating increased travel efficiency, reduced friction of distance, and higher income levels. Novelty: The study provides empirical evidence from a non-metropolitan Indonesian context, extending labor mobility and spatial accessibility theories beyond urban environments. Implications: These results reinforce the strategic role of inclusive, well-integrated transportation infrastructure in regional economic planning and offer a model for similar regions to leverage transport development for labor and productivity gains.Highlight : The development of Trans Jatim Bus Corridor IV improves the efficiency of labor mobility in Lamongan. Public transportation contributes significantly to local economic productivity. This study strengthens the theory of labor mobility in non-metropolitan areas. Keywords : Public Transportation, Labor, Productivity, Lamongan, Trans Jatim